"Made in China 2025": China experience in Industry 4.0. (March 2019) - Li, Jingcheng; Pogodin, Sergey
Abstract: Considering the complexities of the global economic development the leading industrially developed countries approached a consensus in keeping the global economy stable. The latter requires widening the economic collaboration at the global level. China being one of the largest industrial countries in the world declared a new economic initiative "Made in China 2025". This initiative is aimed to transform the traditional opinion on China as a "global factory" and provide it with a new image – "smart advanced production". This article is devoted to a thorough analysis of Program "Made in China 2025", its historical conditions of establishment and implementations prospective. Here it is demonstrated that the program "Made in China 2025" is a new bearing governmental strategy in the national economy which is systematic and aimed to increase the competitiveness of the Chinese economy. It is mentioned that its introduction required solving the following tasks: organic integration of "conventional" and "modern" sectors of Chinese economy; upgrade and optimization of managerial structure of enterprises; development of Chinese industrial standards considering global requirements.